Denying the benefits of the Energy Charter Treaty: Shifting the policy or just the burden of proof? - Crina Baltag (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
This Perspective discusses the proposal under the Energy Charter Treaty reform to move the requirement of investors having "substantial business activity" from Article 17 to the definition of "investor" and proposes possible solutions to clarify how this new provision should be applied in practice.
Keywords: 330